Getting What You Pay For: The Economics of Quality Care for Sexually Transmitted Infections. Issue 1 (January 2016) - Morgan, Jake R.; Drainoni, Mari-Lynn; Sequeira, Shwetha; Sullivan, Meg; Hsu, Katherine K.
Abstract : Background: Understanding the relationship between charges, reimbursement, and quality for sexually transmitted infection (STI) care is necessary to evaluate consequences of shifting patients from STI specialty to nonspecialty settings and to inform quality improvement efforts in this area. Methods: Chart reviews were used to evaluate quality of documented STI care among 450 patients across 5 different clinical settings within a large safety net hospital in Massachusetts for patients presenting with penile discharge/dysuria or vaginal discharge. Charges billed and recouped by the hospital for each visit were extracted from billing records. Univariate methods examined unadjusted differences between quality and other patient and practice characteristics, and charges billed and recouped, whereas a multivariable model predicted the effect of quality on charges and reimbursements after adjusting for potential confounders. Results: Higher documented quality of care was associated with higher charges, with each additional quality point predicting a 9% increase in visit charges. However, these charges were not recouped by the institution, as quality was not associated with higher levels of hospital reimbursement. Among sites of care, the STI clinic had the highest average quality score, as well as the lowest average amount billed and recouped. Conclusions: The relationship we find between documented quality and charges billed may reflect resource use for patient visits. The hospital, however, did not recoup any more on average from higher-quality visits, thus posing an incentive problem for the institution. Our findings suggest that loss of government funds for STI clinics may not be replaced by hospital billing and may lead to lower quality of care. Abstract : Quality of care for sexually transmitted infections significantly predicted higher charges, but not higher revenue for a large safety net hospital. Funding loss for sexually transmitted infection clinics may increase charges and decrease care quality.